Clinical Profile and Prognosis of Hereditary Transthyretin Amyloid Cardiomyopathy: A Single-Center Study in South China - Wang, Shuai; Peng, Wenke; Pang, Min; Mao, Ling; Peng, Daoquan; Yu, Bilian; Wu, Sha; Hu, Die; Yang, Yang; He, Jia; Ouyang, Mingqi (Frontiers in Cardiovascular Medicine, 2022)
Background: Hereditary transthyretin amyloid cardiomyopathy (ATTR-CM) is a genotypically heterogeneous disorder with a poor prognosis. There is limited literature describing the variants responsible for ATTRv in areas outside the United State, the United Kingdom and Europe. This study was performed to describe the clinical characteristics and genotypic profiles of this disease in South China. Methods: This was a single-center retrospective study that evaluated 29 patients with a confirmed diagnosis of hereditary transthyretin amyloid cardiomyopathy enrolled from January 2016 to November 2021. Results: 93.1% patients were male and the median age of symptom onset was 53 (46, 62.5) years old. The initial manifestations of ATTR-CM were cardiovascular symptoms (55.2%), neuropathy (41.4%) and vitreous opacity (3.4%). Phenotypes at diagnosis were mixed (82.8%), predominant cardiac (6.9%), neurological (6.9%) and ophthalmic (3.4%). Poor R-wave progression (41%), pseudo-infarct (31%) and low-voltage (31%) patterns were common findings on electrocardiogram. Unexplained increased wall thickness was observed in all 29 patients, with mean septal and posterior wall thicknesses of 14.25±6.26 mm and 15.34±2.84 mm, respectively. Diastolic dysfunction was also seen in all 29 patients, and 17 (58%) had a restrictive fill pattern at diagnosis. Nine different missense mutations of the TTR gene were found in 29 patients from 23 families, with c.349G＞T (p.Ala117Ser) the most common mutation. The median survival time after diagnosis was 47.6 (95% CI 37.9-57.4) months, with 1, 3 and 5-year survival rates of 91.2%, 74% and 38% respectively. Patients with advanced heart failure (National Amyloidosis Staging stage II/III) had worse survival than stage I [Breslow (Generalized Wilcoxon), χ2=4.693, P=0.03)]. Conclusions: ATTR amyloidosis genotypes and phenotypes are highly heterogeneous. Advanced heart failure predicts a poor prognosis. Understanding the different clinical profiles of ATTR cardiac amyloidosis with different genotype is important to its early recognition.